Fungal Associates of the Xylosandrus compactus (Coleoptera: Curculionidae, Scolytinae) Are Spatially Segregated on the Insect Body - Bateman, Craig; Šigut, Martin; Skelton, James; Smith, Katherine E; Hulcr, Jiri (Environmental entomology, 2016)
Studies of symbioses have traditionally focused on explaining one-to-one interactions between organisms. In reality, symbioses are often much more dynamic. They can involve many interacting members, and change depending on context. In studies of the ambrosia symbiosis-the mutualism between wood borer beetles and fungi-two variables have introduced uncertainty when explaining interactions: imprecise symbiont identification, and disregard for anatomical complexity of the insects. The black twig borer, Xylosandrus compactus Eichhoff, is a globally invasive ambrosia beetle that infests >200 plant species. Despite many studies on this beetle, reports of its primary symbionts are conflicting. We sampled adult X. compactus and infested plant material in central Florida to characterize the fungal symbiont community using dilution series, beetle partitioning, and DNA-based identification. X. compactus was consistently associated with two fungal taxa, Fusarium spp. and Ambrosiella xylebori Multivariate analyses revealed that A. xylebori was strongly associated with the beetle mycangium while Fusarium spp. were associated with the abdomen and external surfaces. The Fusarium spp. carried by X. compactus are not members of the Ambrosia Fusarium Clade, and are probably not mutualists. Fungal community composition of the mycangium was less variable than external body surfaces, thus providing a more consistent fungal inoculum. This is the first report of spatial partitioning as a mechanism for maintenance of a multimember ambrosia fungus community. Our results provide an explanation for discrepancies among previous reports, and suggest that conflicting results are not due to differences in symbiont communities, but due to inconsistent and incomplete sampling.
Keywords: symbióza; Fusarium solani; mutualism; Fungi; DNA, Fungal; nosatcovití; Sequence Analysis, DNA; mycangium; ribozomální DNA; sekvenční analýza DNA; black twig borer; houby; Florida; DNA fungální; Ambrosiella; Weevils; Animals; ženské pohlaví; Fusarium; zvířata; Ascomycota; Symbiosis; DNA, Ribosomal; Female